1998
DOI: 10.2535/ofaj1936.75.2-3_97
|View full text |Cite
|
Sign up to set email alerts
|

Early Organogenesis and Cell Contacts in the Proliferating Hypophysis of the Developing Mouse

Abstract: Summary: The mouse foetal hypophysis which contains the diencephalic downgrowth (Dd) and Rathke's pouch (Rp) was examined using morphological and immunocyto/histo-chemical methods to study the cell-cell and cell-extracellular matrix (ECM) interactions that occur during early organogenesis. While many studies have described that the differentiation of ACTH cells precedes the proliferation of other endocrine cells in the Rp, light and conventional transmission electron microscopic (TEM) investigations have faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…EGFR expression in the cytoplasm and nucleus seemed to indicate downregulation by an internalisation mechanism of EGFR and EGF-receptor complexes in the actively proliferating NP and AP cells. The results of the present study are consistent with those of our previous histological study, which indicated that the mid-foetal murine pituitary is at the active proliferation stage (Han et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…EGFR expression in the cytoplasm and nucleus seemed to indicate downregulation by an internalisation mechanism of EGFR and EGF-receptor complexes in the actively proliferating NP and AP cells. The results of the present study are consistent with those of our previous histological study, which indicated that the mid-foetal murine pituitary is at the active proliferation stage (Han et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…In a previous TEM study, we observed that the proliferating AP was heavily lobulated, but did not differentiate into endocrine cell types in the mid-foetal stage. In addition, we identified the first appearance of MSH cells in the presumptive pars intermedia (Han et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously detected active cell turnover with apoptosis in the developing Dd, Rp and the intervening diencephalic mesenchyme thus brought the presumptive NL and the IL into close approximation. Invasion of the mesenchyme enhanced the lobulation of the AL (Han et al, 1998). In the present study, we examine the localization of TGFa, EGF, EGFR, basic fibroblast growth factor (bFGF; FGF-2) and FGF receptors (FGFR-1 , FGFR-2 and FGFR-3) using optic (light) microscopy (LM) and CLSM to elucidate the temporo-spatial expression of these pro-teins during the morphogenetic/differentiative events of the developing murine hypophysis.…”
mentioning
confidence: 95%
“…In contrast, transmission electron microscopy (TEM) studies have enabled the earliest signs of endocrine activity to be detected in IL cells, which are in close apposition with the NL via a layer of electron-dense intercellular junctions (Han et al, 1998).…”
mentioning
confidence: 99%